Biopsychosocial Factors Affecting the Risk of Musculoskeletal Disorders in Surakarta, Central Java - Dea Linia Romadhoni; Setyo Sri Rahardjo; Dono Indarto (Journal of Epidemiology and Public Health, 2018)
Background: Musculoskeletal Disorders (MSDs) are injuries and disorders that affect the hu